Why Can We Observe a Plateau Even in an Out of Control Epidemic Outbreak? A SEIR Model With the Interaction of n Distinct Populations for Covid-19 in Brazil. - Lazo, M. J.; Cezaro, A. De (Trends in Computational and Applied Mathematics, 2021)
This manuscript proposes a model of $n$ distinct populations interaction structured SEIR to describe the spread of COVID-19 pandemic diseases. The proposed model has the flexibility to include geographically separated communities as well as taking into account aging population groups and their interactions. We show that distinct assumptions on the dynamics of the proposed model lead to a plateau-like curve of the infected population,  reflecting collected data from large countries like Brazil. Such observations aim to the following conjecture: " Covid-19 diseased diffusion from the capitals to the Brazil interior, as reflected by the proposed model, is responsible for plateau-like reported cases in the country". We present numerical simulations of some scenarios and comparison with reported data from Brazil that corroborate with the aforementioned conclusions.